The Value of Experience: Exploring How Retail Innovations Shape Economic Decision-Making Through Consumer Satisfaction - Mahendra, I Made Krishna; Prianthara, I.B. Teddy (Yayasan Riset dan Pengembangan Intelektual, 2025)
The business world is experiencing rapid development, encouraging business actors to adapt to the ever-changing market dynamics. This study aims to analyze the influence of service innovation, product completeness, and store atmosphere on consumer purchasing decisions, with consumer satisfaction as a mediating variable. The research was conducted at Coco Mart Jimbaran with 120 customers as respondents, using Structural Equation Modeling (SEM) for data analysis. The results indicate that service innovation, product completeness, and store atmosphere positively and significantly affect consumer satisfaction. Furthermore, consumer satisfaction has a positive impact on purchasing decisions. However, consumer satisfaction does not significantly mediate the effect of service innovation, product completeness, and store atmosphere on purchasing decisions. This study contributes to the theoretical understanding of the relationship between retail attributes, consumer satisfaction, and purchasing decisions. It also provides practical insights for retail managers to enhance service innovation, improve product offerings, and create an inviting store atmosphere to drive consumer purchasing behavior. Additionally, the findings offer guidance for policymakers in creating regulations that foster retail sector development, such as incentives for service technology innovation and better inventory management practices. With increasing competition in Bali's retail industry, particularly in Badung Regency, these insights provide strategic recommendations for business actors to maintain competitiveness by focusing on customer satisfaction as the key to attracting and retaining loyal customers.